Der neoliberale Leviathan: Eine historische Anthropologie des gegenwärtigen Gesellschaftsregimes - Wacquant, Loïc; Kadritzke, Ulf (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2012)
The anthropology of neoliberalism has become polarised between a hegemonic economic model anchored by variants of market rule and an insurgent approach fuelled by derivations of the Foucaultian notion of governmentality. Both conceptions obscure what is ‘neo’ about neoliberalism: the reengineering and redeployment of the state as the core agency that sets the rules and fabricates the subjectivities, social relations and collective representations suited to realising markets. I propose a via media between these two approaches that construes neoliberalism as an articulation of state, market and citizenship that harnesses the first to impose the stamp of the second onto the third.